The Role of Food Science and Technology for Indonesian Indigenous Food Product Development to Achieve Food Security - Winiati P. Rahayu; Irma Septiani (Indonesian Association of Food Technologists, 2020)
Food insecurity is remaining an unsolved problem since the continuous increase in human populations demands an increased supply of food. The objective of this paper was to present Indonesian indigenous food product development as an answer to the food security problem. It could be conducted by presenting the potentials of indigenous foods, creating advances in food technology, and arranging strategies that needed to develop indigenous food products, particularly as a food technologist. The suggested strategies were: choosing the raw material that is abundantly available in the local area, assessing its superiorities, doing a feasibility study, enhancing the food product’s safety and quality by applying good manufacturing practices and using environmentally friendly packaging, and promoting the products through modern channels such as the supermarket. This would allow nutritious and safe indigenous food products to become competitive and widely impacting food products that can bring food security into a reality.